An Analysis of Directive Function Found In “Enola Holmes” The Movie - Antari, Made Ika Dwi; Winarta, Ida Bagus Gde Nova (STKIP AGAMA HINDU SINGARAJA, 2023)
The aims of this research are to describe the types of directive illocutionary acts function in “Enola Holmes” the movie and to find out the type of directive illocutionary acts function which is mostly used by the characters in this movie. This is descriptive qualitative research. The researcher used observation methods in collecting the data. There were some steps in collecting the data: read the novel several times to understand the plot and examined the dialogue to distinguish the types of directive illocutionary act function that found in the utterance between the characters in the movie. The researcher applied Searle (1979) to analyze the data. The result of the research shows that there are 44 utterances containing directive illocutionary act function. The data were classified into four; ordering (16), forbidding (4), requesting (15), and suggesting (9). Of the total 44 directive illocutionary act function, ordering are the most used types of directives illocutionary act function because the character mostly expressed their utterances by ordering.